MONITORING OF SPECTRAL VARIATIONS OF MIRA-TYPE AND SEMIREGULAR VARIABLE STARS - Rudnitskij, G. M. (Одеські астрономічні публікації, 2017)
The results of monitoring of a sample of late-type variable stars (Mira Ceti-type and semiregulars) are reported. Since 1980 a sample of 60 stars has been observed in the maser line of the H2O molecule at a wavelength of 1.35 cm. These observations are performed on the RT-22 radio telescope of the Pushchino Radio Astronomy Observatory (Moscow Region). Since 1994 optical spectra of some of these stars have also been monitored on the 1.25-meter telescope of the Crimean Laboratory of the Sternberg Astronomical Institute. Regularities in the spectral behavior of the stars are discussed. Variations of the circumstellar H2O masers correlate with the visual light curves (AFOEV and AAVSO data) with a time lag of 0.3–0.4P (P is the star’s period). Flares of the Hα emission noted in R Leo, U Aur, R Cas, and R LMi were followed 1.5–2 years later by corresponding flares of the H2O masers. These phenomena are interpreted as a consequence of propagation of a shock wave driven by stellar pulsation. Alternatively, the shock can be produced by motion of a low-mass satellite (a planet or a brown dwarf) in the inner layer of the circumstellar envelope. The effects of such a satellite on the spectrum and light curve of the primary star are discussed.